(untitled) (Research, Society and Development, 2022)
The species Eleutherine bulbosa Miller (Urb.) has a vast wealth of isolated substances, however, there are few studies of individuals from the Amazon biome, which may present new substances or differentiated biological potentials. Therefore, the aim of the present study was to carry out a phytochemical analysis of E. bulbosa collected in the region of Altamira-PA, in the Amazon biome, and evaluate the biological potential of its extracts. The leaves, flowers and bulbs were dried and then ground. The plant material was then subjected to extraction with organic solvents, and its extracts analyzed by TLC. Through NMR analysis, it was possible to characterize 5 substances: eleutherin (1), eleutherinol-8-O-β-glycoside (2), eleutherol (3), isoeleutherin (4) and eleutherinol (5). The extracts and substances were submitted to antitumor test, however, only the samples that presented sufficient mass for testing were submitted. The hexane extract of the bulb proved to be significant in the antitumor test, causing 50-60% cell death against the tumor strains tested. In the antimicrobial assay, eleuterol and isoeleuterine showed inhibitory action against Staphylococcus aureus and Pseudomonas fluorescens. Eleutherin, eleutherinol and isoeleutherin proved to be important chemical markers of this species, due to their predominance in the plant. Through the results, it is concluded that the plant in question has antimicrobial and antitumor action, however, deeper studies with the isolated substances and extracts are necessary. Still, the results obtained can be used in future comparative studies of the species and genera of the tribe, combined with morphological and phylogeny data, to solve taxonomic problems.